ANALISIS HUKUM TERHADAP MANTAN NARAPIDANA KORUPSI MENJADI CALON LEGISLATIF PASCA PUTUSAN MK NOMOR 59/PUU-XVII/2019 PERSPEKTIF HUKUM ISLAM - Dewi Arnita Sari (IAIN BONE, 2022)
This study uses Normative research, namely research by examining document studies, namely using various secondary data such as statutory regulations, court decisions, legal theory, and can be in the form of opinions of scholars.The results of this study indicate that: (1) when making a regulation or legislation, it must refer to the proper regulations or the 1945 law so that every regulation made does not conflict with other regulations. (2) Every decision given or ruled by the Constitutional Court and the Supreme Court has gone through a long process and has legal certainty that must be obeyed.(3) From the perspective of Islamic law, a former prisoner in a corruption case means that he has violated one of the values of Islamic law such as hifzh al-mal (guarding property) so that it is not used for vanity purposes. So that person no longer needs to be elected or run again to carry out the mandate as a legislative candidate. The recommendation of this research is based on the results of this research, the things that need to be paid more attention. Here we need to be more careful in formulating the regulations, especially the regulations mentioned above relating to the rights of every citizen.